Effects of healing on the seismogenic potential of carbonate fault rocks: Experiments on samples from the Longmenshan Fault, Sichuan, China. Issue 8 (28th August 2015) - Chen, Jianye; Verberne, Berend A.; Spiers, Christopher J.
Abstract Fault slip and healing history may crucially affect the fault seismogenic potential in the earthquake nucleation regime. Here we report direct shear friction tests on simulated gouges derived from a carbonate fault breccia, and from a clay/carbonate fault‐core gouge, retrieved from a surface exposure of the Longmenshan Fault Zone (LFZ) which hosted the 2008 Wenchuan earthquake. The experiments were conducted under dry and hydrothermal conditions, at temperatures up to 140°C, at an effective normal stress of 50 MPa, and involved sequential velocity‐stepping (VS), slide‐hold‐slide (SHS), and velocity‐stepping stages. Dry tests performed on breccia‐derived samples showed no dependence of (quasi) steady state friction (μss) on SHS or VS history, and a log linear relation between transient peak healing (Δμpk) and hold time, or classical "Dieterich‐type" healing behavior. By contrast, all experiments conducted under hydrothermal conditions were characterized by "non‐Dieterich" healing behavior. This included (1) an increase in μss upon resliding after a hold period and (2) an increase in friction rate parameter (a − b), after SHS testing. Comparison with previous results suggests that the healing behavior seen in our wet tests may be attributed to solution transfer processes occurring during hold periods. Our findings imply that the shallow portions of faults with carbonate/clay‐rich cores (e.g., the LFZ) can heal much faster than previously recognized, while the upper limit of the seismogenic zone may migrate to deeper levels during interseismic periods. These effects have important implications for understanding the seismic cycle in tectonically active carbonate terrains.